The Examination of Special Education Teachers' Views On Teaching Play Skills to Children With Autism Spectrum Disorders - Ayşe Çigdem GÜLVEREN; Şerife YÜCESOY ÖZKAN; Nuray ÖNCÜL (Anı Publishing, 2022)
The current study aims to understand how the special education teachers define play skills, examine their views on the teaching of play skills to children with ASD, and determine their experiences in teaching play skills to children with ASD. The phenomenological design, one of the qualitative research methods, was used in the study. The participants were 14 special education teachers working in a special education school. A semi-structured interview was used to collect data. The findings reveal that the special education teachers defined the play skills as entertaining and teaching activities; they found the play skills are essential and should be taught to children with ASD. They also think that the play affects the psychomotor, language and communication, social-emotional, and cognitive development of children with ASD positively, play skills can be taught in any age and anywhere by teachers, parents, and caregivers. The findings also indicate that most of the teachers involved play skills training in individualized education programs of their students. They used peer tutoring, in-vivo and video modelling, dramatization, response prompt strategies, and incidental teaching as an intervention. Based on the results, it can be suggested that teachers should receive training and seminars on teaching play skills to children with ASD and that teachers should be encouraged and supported to include play skills goals when designing an individualized educational program for children with ASD.